Method Development and Validation for the Simultaneous Estimation of Rosuvastatin and Amlodipine in Bulk and its Formulation using Reverse-Phase High-Performance Liquid Chromatography - Peddapalli, Himabindu (Asian Journal of Pharmaceutics (AJP), 2019)
Background: High-performance liquid chromatography (HPLC) is basically a highly improved form of column liquid chromatography. Instead of a solvent being allowed to drip through a column under gravity, it is forced through under high pressures of up to 400 atmospheres which makes it much faster. All chromatographic separations including HPLC is based upon the resolution of the sample constituents as per the difference in their relative affinities towards stationary phase and mobile phase used. Aim: A simple, specific, accurate, and precise reverse-phase HPLC method was developed and validated for the estimation of rosuvastatin and amlodipine (Rosudapin) in pharmaceutical dosage form. Materials and Methods: An Aquasil column reversed phase C-18, 5 μm column having 4.6 mm × 250 mm i.d. in gradient mode, with mobile phase containing HPLC grade acetonitrile:phosphate buffer (pH 3.8):methanol in proportion 30:60:10 v/v, was used. The flow rate was 1 ml/min and effluents were monitored at 251 nm using PDA detector. Linearity was observed over a range of 5–25 μg/mL of rosuvastatin and 2.5–12.5 μg/mL of amlodipine, respectively. Results and Discussion: The method was validated for linearity, accuracy, precision, limit of detection, limit of quantitation, robustness, and ruggedness. The limit of detection and estimation of analytes was found to be 3.1 μg/ml and 2.98 μg/ml, and the limit of quantification of analytes was found to be 102 μg/ml and 9 μg/ml, respectively, for rosuvastatin and amlodipine. Conclusion: The proposed method was successfully applied for the quantitative determination of rosuvastatin and amlodipine in pharmaceutical dosage form.